Purification and immunological characterization of a major low-molecular-weight lipoprotein from Borrelia burgdorferi. - Katona, L I (1992)
Borrelia burgdorferi resembles gram-negative bacteria in having both cellular and outer membranes. We previously showed that a lipopolysaccharide (LPS)-like material could be extracted from B. burgdorferi with phenol-chloroform-petroleum ether (PCP). The PCP extract of B. burgdorferi exhibited biological activity in several in vitro assays (e.g., mitogenicity, pyrogenicity, and cytokine release). These activities suggested the presence of endotoxin. The PCP extract of B. burgdorferi, however, also contained a small amount of protein. Preliminary studies showed that monoclonal antibody prepared against this protein inhibited the mitogenic activity of the PCP extract toward murine spleen cells. The current study was therefore undertaken to characterize this protein and to establish methods for its separation from the LPS. The PCP-extracted protein consisted of a single, low-molecular-weight lipoprotein (apparent M(r), 10,000 by sodium dodecyl sulfate-polyacrylamide gel electrophoresis) (SDS-PAGE). By protein analysis, it accounted for 2% of the dry weight of defatted cells, thus making it a major constituent of the spirochete. It was purified from the LPS by initial extraction into 10% Triton X-100 followed by immunoaffinity chromatography in the presence of detergent. On removal of the LPS, the purified lipoprotein formed aggregates stable to SDS-PAGE which were detectable on Western blots (immunoblots) probed with either the monoclonal antibody or polyclonal antiserum. From a plot of the aggregate molecular weight versus aggregate size, a monomer molecular weight of 7,500 was obtained. Indirect immunofluorescence with the monoclonal antibody showed that the lipoprotein was exposed at the surface of the spirochete in only a small percentage of cells. The lipoprotein was present in several strains of B. burgdorferi but absent in other Borrelia spp., treponemes, and gram-negative human pathogens, indicating species specificity.